A Call to Higher Things. Issue 6 (1st January 2013) - Goodman, Lenn E.
Abstract: Seeking a responsible middle ground between complaisance and the "religious totalitarianism" of Sayyid Qutb, Miroslav Volf proposes a proper role for religion as a faithful advisor in the public square and an inspired one in the corridors of conscience. But he seems to lose patience with that theme without addressing John Rawls' case for silencing religious counsels-or engaging the strident atheism of Dennett, Dawkins, Hitchens, or Grayling, and he takes Qutb more as a foil than an adversary to be grappled with directly. Turning away from debates over religion's proper public role he catalogues the "malfunctions" of faith, sidestepping many of today's more burning issues in favor of a generic call to "lives of integrity"-while acknowledging that we mortals are "powerless against the lure of evil, " too often seconded by "the power of the systems that surround us." Prayer, Volf argues, finds its best use when we ask to be made "willing, capable, and effective instruments in God's hand." One only wishes he had been more explicit and more ready for down and dirty argument with those who reject the very idea of prayer and with those who imagine they become God's best instrument when holding an incendiary device.